Unexpected Bone Metastases from Thyroid Cancer - Sandra Gibiezaite; Savas Ozdemir; Sania Shuja; Barry McCook; Monica Plazarte; Mae Sheikh-Ali (Case Reports in Endocrinology)
Objective. To present a complicated case of differentiated thyroid carcinoma (DTC) with metastases to the skull that was evident on I-131 whole body scan (WBS) but negative on other imaging modalities in a low risk patient. Methods. We will discuss clinical course, imaging, pathological findings, and treatment of the patient with skull metastasis from DTC. Pertinent literature on imaging and pathology findings as well as radioactive iodine (RAI) treatment impact on quality of life and survival in patients with bone metastases from DTC will be reviewed. Results. The patient is a 37-year-old woman with a diagnosis of DTC who had focal areas of increased uptake in the head on WBS with no correlative findings on CT and MRI. Initially, false positive findings were suspected since patient had a low risk for developing metastases. However, the persistent findings on post-RAI treatment WBS, following two courses of treatment, were highly concerning for metastatic bone disease. WBC performed 6 months following the second RAI treatment revealed resolution of the findings. Conclusions. False positive findings in WBS are frequent and may be due to contamination, perspiration, or folliculitis of the scalp as well as benign lesions such as meningioma, hematoma, cavernous angioma, and metallic sutures. However, metastatic disease should always be considered even if the patient has low risk of distant metastatic disease and correlative images do not support the diagnosis. RAI therapy appears to improve the survival rates and quality of life of thyroid cancer patients with bone metastases based on retrospective studies.